Enhancing the Capacity for Classroom Action Research Utilizing Artificial Intelligence Among Teachers at MAN Bengkayang - Sari, Nopita; Zuraya, Helva (AT-TURATS, 2024)
Issues Examined in this article: Firstly, the level of comprehension and awareness among teachers at MAN Bengkayang regarding the significance of Classroom Action Research (CAR) in enhancing the quality of education; secondly, the obstacles encountered by teachers at MAN Bengkayang in conducting CAR; thirdly, the identification of effective strategies to improve the capacity of teachers at MAN Bengkayang in implementing AI-based CAR; and fourthly, the extent to which AI-based CAR training programs contribute to the enhancement of teachers' professional competencies at MAN Bengkayang. This article is derived from a community engagement initiative grounded in research utilizing the Participatory Action Research (PAR) methodology. The findings are as follows: first, teachers at MAN Bengkayang exhibit a limited understanding of Classroom Action Research (CAR). Second, teachers at MAN Bengkayang face significant challenges in balancing teaching responsibilities with administrative tasks, which impede the effective implementation of CAR. Third, effective strategies to enhance teachers' competencies in conducting AI-based CAR should encompass technological training, fostering collaboration among teachers, leveraging data for evaluation and feedback, integrating technology into the curriculum, and ensuring the availability of adequate infrastructure. Fourth, AI-based CAR training programs have substantially improved the professional competencies of teachers at MAN Bengkayang. Before participating in the AI-based CAR training, the professional competency of teachers at MAN Bengkayang was assessed at 68.12%, categorized as "adequate." Following the training, this competency level increased to 90.1%, categorized as "excellent."Isu yang dibahas dalam artikel ini: Pertama, tingkat pemahaman dan kesadaran guru di MAN Bengkayang terhadap pentingnya Penelitian Tindakan Kelas (PTK) dalam meningkatkan kualitas pendidikan. Kedua, hambatan yang dihadapi oleh guru di MAN Bengkayang dalam melaksanakan PTK. Ketiga, identifikasi strategi efektif untuk meningkatkan kapasitas guru di MAN Bengkayang dalam menerapkan PTK berbasis AI. Keempat, sejauh mana program pelatihan PTK berbasis AI berkontribusi pada peningkatan kompetensi profesional guru di MAN Bengkayang. Artikel ini berasal dari kegiatan pengabdian masyarakat yang didasarkan pada penelitian dengan menggunakan metode Participatory Action Research (PAR). Temuan penelitian adalah sebagai berikut: Pertama, Guru di MAN Bengkayang menunjukkan pemahaman yang terbatas tentang Penelitian Tindakan Kelas (PTK). Kedua, Guru di MAN Bengkayang menghadapi tantangan besar dalam menyeimbangkan tanggung jawab mengajar dengan tugas administratif, yang menghambat pelaksanaan PTK secara efektif. Ketiga, Strategi efektif untuk meningkatkan kompetensi guru dalam melaksanakan PTK berbasis AI meliputi: pelatihan teknologi, mendorong kolaborasi antar guru, memanfaatkan data untuk evaluasi dan umpan balik, mengintegrasikan teknologi ke dalam kurikulum, serta memastikan ketersediaan infrastruktur yang memadai. Keempat, Program pelatihan PTK berbasis AI secara signifikan meningkatkan kompetensi profesional guru di MAN Bengkayang. Sebelum mengikuti pelatihan PTK berbasis AI, kompetensi profesional guru di MAN Bengkayang dinilai sebesar 68,12% (kategori "cukup"). Setelah pelatihan, tingkat kompetensi ini meningkat menjadi 90,1% (kategori "sangat baik").